2011
DOI: 10.1590/s1981-81222011000300006
|View full text |Cite
|
Sign up to set email alerts
|

Artefatos de miriti (Mauritia flexuosa L. f.) em Abaetetuba, Pará: da produção à comercialização

Abstract: No estuário amazônico, a palmeira Mauritia flexuosa L. f. (miriti) é conhecida por fornecer matéria-prima para a confecção de cestaria e brinquedos, ambos de relevância econômica e cultural para a população local. Este estudo teve como objetivo realizar um levantamento a respeito da produção e comercialização dos dois principais artefatos - paneiros e brinquedos de miriti, no município de Abaetetuba, Pará. A pesquisa foi conduzida na comunidade ribeirinha de Cutininga e em duas associações de artesãos da sede … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 3 publications
0
7
1
3
Order By: Relevance
“…The literature indicates that the influence of age on the use of resources may differ among locations [7,24], with older people holding more knowledge [4,23,26,48,54], a result not recorded in the study of Balslev et al [8] or in the current study. In addition, Muller et al [20] found that age alone does not explain all standards of ethnobotanical knowledge in Southeast Nigeria, and that consideration of the gender of people is necessary.…”
Section: Discussioncontrasting
confidence: 51%
“…The literature indicates that the influence of age on the use of resources may differ among locations [7,24], with older people holding more knowledge [4,23,26,48,54], a result not recorded in the study of Balslev et al [8] or in the current study. In addition, Muller et al [20] found that age alone does not explain all standards of ethnobotanical knowledge in Southeast Nigeria, and that consideration of the gender of people is necessary.…”
Section: Discussioncontrasting
confidence: 51%
“…Although there is no evidence of domestication of M. flexuosa , it is widely used by indigenous groups and local communities along rivers, who refer to it as the “tree of life” because it provides a variety of resources and it is consumed daily as a food staple (Barros & Da Silva, 2013). This palm is also used for raw material for construction and for different handicrafts (Santos & Coelho‐Ferreira, 2011) and its fruits, leaves, and seeds are sold widely in markets (Gilmore, Endress, & Horn, 2013). Mauritia flexuosa has been termed a “hyperdominant” species (Steege et al., 2013), in which population densities are five times higher than expected by chance, and that has recently been attributed to human use and tending practices associated to its use (Levis et al., 2017; Rull & Montoya, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This palm is also used for raw material for construction and for different handicrafts (Santos & Coelho-Ferreira, 2011) and its fruits, leaves, and seeds are sold widely in markets (Gilmore, Endress, & Horn, 2013). Mauritia flexuosa has been termed a "hyperdominant" species (Steege et al, 2013), in which population densities are five times higher than expected by chance, and that has recently been attributed to human use and tending practices associated to its use (Levis et al, 2017;Rull & Montoya, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Essa é uma prática desenvolvida por diversas comunidades na Amazônia, sendo que, em alguns locais, representa importante fonte de geração de renda e comércio (SANTOS; COELHO-FERREIRA, 2011). No caso do artesanato em Igarapé Grande, a produção desenvolvida tanto por homens, quanto mulheres é uma alternativa de complementação de renda e de suporte às demais atividades, tendo em vista a produção de ferramentas.…”
Section: Os Agricultores Da Comunidade Igarapé Grandeunclassified